Growth and potential damage of human bone-derived cells cultured on fresh and aged C60/Ti films - Kopova, Ivana; Lavrentiev, Vasily; Vacik, Jiri; Bacakova, Lucie (PloS one, 2015)
Thin films of binary C60/Ti composites, with various concentrations of Ti ranging from ~ 25% to ~ 70%, were deposited on microscopic glass coverslips and were tested for their potential use in bone tissue engineering as substrates for the adhesion and growth of bone cells. The novelty of this approach lies in the combination of Ti atoms (i.e., widely used biocompatible material for the construction of stomatological and orthopedic implants) with atoms of fullerene C60, which can act as very efficient radical scavengers. However, fullerenes and their derivatives are able to generate harmful reactive oxygen species and to have cytotoxic effects. In order to stabilize C60 molecules and to prevent their possible cytotoxic effects, deposition in the compact form of Ti/C60 composites (with various Ti concentrations) was chosen. The reactivity of C60/Ti composites may change in time due to the physicochemical changes of molecules in an air atmosphere. In this study, we therefore tested the dependence between the age of C60/Ti films (from one week to one year) and the adhesion, morphology, proliferation, viability, metabolic activity and potential DNA damage to human osteosarcoma cells (lines MG-63 and U-2 OS). After 7 days of cultivation, we did not observe any negative influence of fresh or aged C60/Ti layers on cell behavior, including the DNA damage response. The presence of Ti atoms resulted in improved properties of the C60 layers, which became more suitable for cell cultivation.
Keywords: Tissue Engineering; poškození DNA; viabilita buněk; DNA Damage; Cell Line, Tumor; Cell Proliferation; fullereny; reaktivní formy kyslíku; osteoblasty; titan; Titanium; Osteoblasts; Cell Survival; buněčná adheze; tkáňové inženýrství; Reactive Oxygen Species; Time Factors; lidé; Humans; časové faktory; Tissue Scaffolds; proliferace buněk; tkáňové podpůrné struktury; nádorové buněčné linie; Cell Adhesion; Fullerenes